2019
DOI: 10.1002/alr.22272
|View full text |Cite
|
Sign up to set email alerts
|

Atopy in chronic rhinosinusitis: impact on quality of life outcomes

Abstract: Background: Chronic rhinosinusitis (CRS), in particular with nasal polyps (CRSwNP), has been linked with skewed T-helper 2 and immunoglobulin E (IgE)-mediated allergic responses. The role of atopy in CRS, however, remains unclear. Correlations between immunological allergic markers and patient-reported outcomes measures (PROMs) were investigated. Methods:A cross-sectional study of adult patients with CRS undergoing endoscopic sinus surgery was conducted. Immunological allergic markers included automated immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Other studies have found no significant association between CRSwNP and allergy. Study findings include similar rates of hypersensitivity between CRSwNP and CRSsNP groups; 1385 similar incidence of allergy and endotype profiles between CRSwNP and CRSsNP; 1386 no difference in symptoms among allergic and non‐allergic CRSwNP patients during pollen season 1387 no differences in nasal polyp size, CT scores, symptoms, or recurrence of disease between atopic and non‐atopic CRSwNP patients 1388 or difference in presenting symptoms or post‐operative course of CRSwNP patients based on allergic status 1389,1390 In contrast, 1 study found increased rates of atopy in CRSwNP patients, though no significant difference in symptoms scores 1391 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 98%
“…Other studies have found no significant association between CRSwNP and allergy. Study findings include similar rates of hypersensitivity between CRSwNP and CRSsNP groups; 1385 similar incidence of allergy and endotype profiles between CRSwNP and CRSsNP; 1386 no difference in symptoms among allergic and non‐allergic CRSwNP patients during pollen season 1387 no differences in nasal polyp size, CT scores, symptoms, or recurrence of disease between atopic and non‐atopic CRSwNP patients 1388 or difference in presenting symptoms or post‐operative course of CRSwNP patients based on allergic status 1389,1390 In contrast, 1 study found increased rates of atopy in CRSwNP patients, though no significant difference in symptoms scores 1391 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 98%
“…Although asthma in AERD patients tends to segregate in the severe persistent category, patients with AERD can have mild or moderate persistent asthma or even intermittent asthma, which may be missed if not adequately assessed. Furthermore, comorbid AR and asthma may predict severity of disease and increased symptom burden . A recent prospective case‐control study demonstrated that CRSwNP with comorbid AR and asthma was associated with increased eosinophil ratios and a higher risk of polyp recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comorbid AR and asthma may predict severity of disease and increased symptom burden. 30 A recent prospective case-control study demonstrated that CRSwNP with comorbid AR and asthma was associated with increased eosinophil ratios and a higher risk of polyp recurrence. 31 Therefore, it is necessary to obtain a thorough allergy and asthma history when CRSwNP is identified.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the effect of atopy on quality of life is ill‐defined. In the article by Ho et al., the authors performed a cross‐sectional study on CRS patients undergoing functional endoscopic sinus surgery and specifically assessed the impact of atopy on disease‐specific quality of life. Atopy was defined by either a positive test for allergen‐specific immunoglobulin E (IgE) or an elevation in total IgE, and quality of life metrics were assessed using the 22‐item Sino‐Nasal Outcome Test (SNOT‐22).…”
mentioning
confidence: 99%